Slow ventricular tachycardia presenting with acute liver failure - Wannhoff, Andreas; Nußhag, Christian; Stremmel, Wolfgang; Merle, Uta (SAGE open medical case reports, 2017)
Objectives: Cardiac hepatopathy is an important differential diagnosis of acute liver failure. Slow ventricular tachycardia (slow VT) is a ventricular tachycardia (VT), in which heart rate is below the typical frequency of VT. We here report a case of acute liver failure in a patient with slow VT.Methods:The 64-year old male patient with history of cardiac pacemaker implantation for complete atrioventricular block was referred to our intensive care unit because of acute liver failure.Results:Workup identified cardiac failure as cause of hepatopathy; however, reason for cardiac failure remained unknown even after left heart catheterization with coronary angiography. Finally, the analysis of cardiac pacemaker recordings led to the diagnosis of slow VT. This could not be terminated with either electric cardioversion or pharmacological treatment, and the patient died of cardiac failure.Conclusion:Diagnosis of VT can be challenging if occurring at unexpected slow heart rates. Analysis of pacemaker recordings could help to make the diagnosis of slow VT.
Gesehen am 11.11.2024